MUHAMMAD QUTHB’S THOUGHTS ABOUT EXEMPLARY VALUES IN ISLAMIC EDUCATION - Gumilang, Wahyu (Tawazun: Jurnal Pendidikan Islam, 2018)
This research is focused on the ideas of Muhammad Quthb of exemplary values in Islamic education. This research uses qualitative descriptive analytical approach that emphasizes the analysis on the process of deductive and inductive inference as well as the analysis of the dynamics of the relationship between the observed phenomena, using scientific logic. Muhammad Quthb said that the purpose of education in Islam is to form human beings to be righteous or good that is beings human comprehensively. To realize these goals will require a method of educating that one of them is to educate by example. Muhammad Quthb thought that the example is one of the techniques that effective and successful to be used. These Theories of education contained in the book is still not sufficiently effective when these theories cannot be translated (implemented) in real life in the form of behavior, gestures, expressions of taste and though. Therefore planting exemplary values in the educational process becomes very important to establish a righteous man. The exemplary values to be instilled in the educational process are the values of piety, khusyu’, shy, gentle and compassion to fellow Muslims and hard against the bad deeds and perpetrators of evil, tawadhu ’, patience, brotherhood in Islam, love, purity and beauty, honesty and trustworthy. Keywords : values, ideals, Muhammad Quthb